Banking Digitalization as an Approach to Enhancing Financial Inclusion: An Analytical Study of the Role of Banking Services in Empowering the Unbanked - Mohammed Muneam Ali; Yasir Majeed Dahdooh; Layth Abdul Hamza Ghazzay (Research Parks Publishers, 2026)
The research aims Search to analysis role digitization Banking in Strengthening Inclusion Financial in Iraq, from during evaluation effect Services Banking Digital on Enabling Categories not Included By system Financial Official . Approved . Search on Methodology My analysis quantitative Based on to Data Sample Panel Data from banks Commercial Iraqi during The period 2015–2024 , included Indicators Inclusion Financial like number the accounts Banking Open, size Transactions Electronic, and percentage Loans The guide For individuals and companies The small one, In exchange Indicators For digitization Banking It was represented in spread Services Banking via The phone Mobile and the internet and size Investments in Structure Technology . It was Use Models decline For data Tablet ( Fixed Effects) Random Effects ( add ) to a test Haussmann To check from The model The most suitable, as It was completed Asylum to Models Variables Instrumental ( IV ) treatment probability Link reverse between digitization Height demand on Services Banking . It showed Results presence effect positive This indication Statistics For digitization Banking in Strengthening Inclusion Financial from during more Use Transactions Electronic and facilitation to open the accounts on Distance . As well. She showed Results Contrast in size impact between banks Government And private, so He was impact greater in banks Private The most flexibility in adoption Technologies Modern. And concludes Search to that digitization Banking Represent path effective To expand a base Inclusion Financial in Iraq, Provided to support Structure Infrastructure Digital and strengthening trust Services Electronic . And it offers Search Number from Recommendations For manufacturers decision and banks To improve Access to Services Finance and enabling Categories not Included Banking-wise.